In varietate concordia - United in diversity: An analyze of the EU environment according to its motto - Roland Brandtjen (IU Internationale Hochschule, 2023)
In Varietate Concordia - United in diversity, the motto of the European Union is often mentioned by some politicians and in EU-related literature. However, one wonders what this motto actually means for the EU and how it is implemented in reality. To this end, the terminology of the motto is first examined due to the multilingualism of the EU. Differences between diversity and variety as well as between united and harmonized are examined in more detail. This paper attempts to examine and fill a scientific gap on this topic by means of an adapted SPELIT analysis, the PLISE method. For the most part, the specialist literature is consulted. On the topic of the social environment, quantitative results of a survey in German Länder, Spanish Autonomous Communities, French and Italian regions, and the countries of the United Kingdom plus Cornwall are displayed. Finally, after the concluding section and the bibliography, the official translation of the motto into 73 official, co-official, recognised and minority languages is listed in the appendix.
Keywords: 650; United in diversity; European Union; SPELIT / PLISE; Blue Banana; Harmonization